Design and Verification of a Penetration System Used for Constructing the Sampling Channel. Issue 1 (1st December 2022) - Ma, Ruqi; Ma, Rulin; Sun, Kang; Chao, Ma; Jiang, Shuiqing
Abstract: Based on the analysis of the water ice sampling system design at the lunar permanent shadow region(PSR), a rapid sampling channel construction method based on kinetic energy penetration was proposed, and an engineering prototype of the penetrator system based on the conversion of chemical energy and kinetic energy was developed, which can solve the problem that the subsurface lunar water ice is too difficult to sample quickly due to its significantly enhanced mechanical properties. Based on the mechanical properties boundary of lunar soil water ice, the performance of the engineering prototype was tested and verified. The test results show that the penetrating system developed in this paper can achieve rapid penetration into the lunar soil with uniaxial compressive strength of about 30MPa without consuming power consumption; the penetrating depth can reach 234mm, and the penetrating time is less than 1s. The penetrating system can rapidly construct sampling channels, which can effectively solve the problem of the high-hardness water ice samples located at the subsurface layer of the lunar soil that can be efficiently exposed faced by in-situ water ice sampling in the permanent shadow region.